2013
DOI: 10.7314/apjcp.2013.14.3.1597
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of CA15-3, AFP, CA19-9 and CEA Tumor Markers in Cancer Care and Treatment of Patients with Impaired Renal Function on Hemodialysis

Abstract: Since renal failure causes decrease in tumor marker excretion, use of these markers in cancer care and treatment in patients with renal insufficiency or hemodialysis is controversial. The aim of this study was to investigate differences of serum levels of tumor markers CA15-3, AFP, CA19-9 and CEA in patients with impaired renal function. A total of 100 patients referred to the Tabriz Immam Reza and Amiralmomenin hospital from June 2010 to November 2011 were selected for study. Subjects were divided to 3 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…In addition, patients undergoing dialysis may be less likely to undergo tumor marker measurements even if they are at risk of HCC, possibly due to lower awareness on the importance of measuring tumor markers during HCC surveillance . Although in this study there was no difference in serum AFP levels between the dialysis and non‐dialysis groups, possibly due to the influence of renal function on AFP , we found that serum DCP levels, which are reportedly not influenced by renal function , were significantly higher at HCC diagnosis in patients undergoing dialysis than in the non‐dialysis controls. Furthermore, it may be difficult at dialysis clinic to assess the risk of developing HCC accurately, based on the degree of liver fibrosis or hemosiderosis, age, or status of hepatitis viruses including viral genotype or viral loads.…”
Section: Discussioncontrasting
confidence: 71%
“…In addition, patients undergoing dialysis may be less likely to undergo tumor marker measurements even if they are at risk of HCC, possibly due to lower awareness on the importance of measuring tumor markers during HCC surveillance . Although in this study there was no difference in serum AFP levels between the dialysis and non‐dialysis groups, possibly due to the influence of renal function on AFP , we found that serum DCP levels, which are reportedly not influenced by renal function , were significantly higher at HCC diagnosis in patients undergoing dialysis than in the non‐dialysis controls. Furthermore, it may be difficult at dialysis clinic to assess the risk of developing HCC accurately, based on the degree of liver fibrosis or hemosiderosis, age, or status of hepatitis viruses including viral genotype or viral loads.…”
Section: Discussioncontrasting
confidence: 71%
“…A recent study has shown the use of tumor biomarkers in cancer patients with impaired renal function should be done with precaution. 15 This highlights the importance of detecting early kidney damage by testing urinary MA in cancer patients for interpreting the results of tumor biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, routine screening of the transplant population with serum tumor markers was not useful because of the low sensitivity and specificity of these tests. In addition, studies by Estakhri et al 2 and Tzitzikos et al 22 showed that CA 19-9 with presence of increased levels is not specific for neoplasms after hemodialysis treatment. Wood et al 28 concluded that single isolated determinations of CA 125 and CA 19-9 are not reliable indicators of malignancy in renal transplant patients.…”
Section: Ca 19-9 and Ca 50 In Chronic Kidney Diseasementioning
confidence: 97%
“…Tumor marker concentrations in healthy individuals is low or zero, and its increasing concentrations suggest the incidence of related tumor (Figure 1). 2 Tumor markers are widely used in monitoring cancer patients and for screening of certain tumors. It has recently been shown that concentrations of some tumor markers are higher in patients with chronic kidney disease (CKD) than in healthy subjects ( Table 1).…”
Section: Definition Of Serum Tumor Markersmentioning
confidence: 99%